Efficiency of quantitative methods of coproovoscopy for eimeriosis in rabbits - Mykhailiutenko, S.; Kulynych, S.; Peleno, R.; Leno, M.; Zhulinska, O.; Gutyj, B. (Scientific Progress & Innovations, 2022)
Scientific and technical progress today is a significant driving force in conducting accurate diagnostic studies in veterinary medicine, including coproovoscopic ones. Most of the known methods of coproscopy are aimed at detecting invasive elements in the feces of various animal species and are divided into qualitative and quantitative. The latter are more effective because they give a clear understanding to a qualified researcher and a doctor of veterinary medicine about the level of colonization of the organism by the causative agents of parasitic invasions. The above allows the veterinary medicine doctor to establish a diagnosis promptly, prescribe medicinal drugs for animals, and develop schemes of preventive measures. Therefore, studying the effectiveness of coproovoscopy methods for various parasitic diseases is an important area of research. The study aimed to determine the diagnostic efficiency of the lifelong methods of quantitative coproovoscopic diagnosis for eimeriosic infestation in rabbits. The work was performed based on the Laboratory of Parasitology of the Poltava State Agrarian University. In laboratory conditions, testing of the diagnostic efficiency of 4 methods of quantitative coproovoscopic diagnosis was carried out: Melnychuk et al., 2020 (a patent of Ukraine for a utility model № 141207); Stoll, 1959; Trach, 1992; Taylor et al., 2015. It was experimentally proven that, among the studied methods, the quantitative method of coproovoscopic diagnosis by Melnychuk et al. has the highest diagnostic efficiency. The execution of the method under the methodology described in the patent made it possible to detect the largest number of Eimeria oocysts in rabbit feces – 1296.00±391.13 oocysts/g, with their minimum and maximum fluctuations from 330 to 1902 oocysts/g. The use of coproovoscopy methods by Stoll, Trach, and Taylor et al., according to the implementation recommendations, made it possible to detect, on average, 510.00±240.39, 514.40±275.3, and 939.60±439.23 oocysts in 1 g of feces, respectively, for their minimum and maximum values from 144 to 1728 oocysts/g. It was established that the quantitative method of coproovoscopic diagnosis of Melnychuk et al., based on the indicators of the average number of eimeries oocysts detected in 1 g of feces compared to the methods of Stoll, Tracha, and Taylor et al. turned out to be better by 60.65 %, 60.34 % (P<0.001) and 27.5 % (P<0.01), respectively. The obtained data have important practical significance for veterinary medicine doctors when choosing the most effective method of diagnosis of eimeriosic infestation of rabbits.